Some Issues for the Assessment of Tax Fairness and Tax System Efficiency - Yeganyan, Arpine (Bulletin of Yerevan University G: Economics, 2022)
This article analyzes the relationship between justice and economic and tax efficiency. The method of scientific analysis of theoretical material, taking into account topical issues of social justice and economic and, in particular, tax efficiency, analyzes the hypothesis that a fair tax system contributes to economic efficiency. Taxes are one of the ways to redistribute income. However, every re-distribution faces a problem of justice and efficiency. Justice is the basic principle of social relations. Inefficiency is not a direct result of a lack of resources. Any inequality of opportunity leads to inefficiency; on the contrary, equality contributes to economic efficiency. Resolving the contradictions of justice, that is, meeting the needs of the individual, protecting interests, and meeting the interests of everyone, that is, efficiency, achieving balance, can generally reduce the severity of many conflicts in modern society. Using the method of scientific analysis of theoretical material, the hypothesis that a fair tax system is economically effective is researched.
Keywords: tax system; tax policy; economic efficiency; tax burden; tax privilege; tax proportionality; social justice